2017 IEEE 20th International Conference on Intelligent Transportation Systems (ITSC) 2017
DOI: 10.1109/itsc.2017.8317798
|View full text |Cite
|
Sign up to set email alerts
|

A type-2 fuzzy modelling framework for aircraft taxi-time prediction

Abstract: Knowing aircraft taxi-time precisely a-priori is increasingly important for any airport management system. This work presents a new approach for estimating and characterising the taxi-time of an aircraft based on historical information. The approach makes use of the interval type-2 fuzzy logic system, which provides more robustness and accuracy than the conventional type-1 fuzzy system. To compensate for erroneous modelling assumptions, the error distribution of the model is further analysed and an error compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In 2014, Ravizza et al [47] compared and analyzed the results of multivariate linear regression, least median squared linear regression, Support Vector Regression, M5 model tree, and TSK fuzzy model, and the results showed that the TSK fuzzy rule system model outperforms the other models in terms of prediction accuracy. In 2017, Obajemu et al [51] utilized a type-2 fuzzy logic system to establish a taxi time prediction model with the innovative introduction of speech information and, compared to the traditional one-layer fuzzy system, the method improves the taxi time prediction accuracy and generalization ability, with stronger robustness and accuracy. Subsequently, Chen [56] improved the previous work; after mathematically processing the influencing factors of taxi time delays, a multi-objective fuzzy rule-based system was added to the uncertainty factors in the aircraft taxiing process in the historical data in order to reduce the delays and conflicts in the taxiing process, which in turn made the taxi time prediction more accurate and resilient.…”
Section: Fuzzy Rule Systemmentioning
confidence: 99%
“…In 2014, Ravizza et al [47] compared and analyzed the results of multivariate linear regression, least median squared linear regression, Support Vector Regression, M5 model tree, and TSK fuzzy model, and the results showed that the TSK fuzzy rule system model outperforms the other models in terms of prediction accuracy. In 2017, Obajemu et al [51] utilized a type-2 fuzzy logic system to establish a taxi time prediction model with the innovative introduction of speech information and, compared to the traditional one-layer fuzzy system, the method improves the taxi time prediction accuracy and generalization ability, with stronger robustness and accuracy. Subsequently, Chen [56] improved the previous work; after mathematically processing the influencing factors of taxi time delays, a multi-objective fuzzy rule-based system was added to the uncertainty factors in the aircraft taxiing process in the historical data in order to reduce the delays and conflicts in the taxiing process, which in turn made the taxi time prediction more accurate and resilient.…”
Section: Fuzzy Rule Systemmentioning
confidence: 99%